2013
DOI: 10.1371/journal.pone.0059308
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging at 7T Reveals Common Events in Age-Related Sarcopenia and in the Homeostatic Response to Muscle Sterile Injury

Abstract: Skeletal muscle remodeling in response to various noxae physiologically includes structural changes and inflammatory events. The possibility to study those phenomena in-vivo has been hampered by the lack of validated imaging tools. In our study, we have relied on multiparametric magnetic resonance imaging for quantitative monitoring of muscle changes in mice experiencing age-related sarcopenia or active regeneration after sterile acute injury of tibialis anterior muscle induced by cardiotoxin (CTX) injection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
64
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 29 publications
7
64
0
3
Order By: Relevance
“…These findings clearly showed that myeloid HIFs are not essential for skeletal muscle regeneration. Although the CTX-induced MRI changes observed in this study are in line with those recently reported in the literature (33), we further demonstrated that the increase of FA occurring 7 d after injury (33) was actually related to the decreased l 2 and l 3 values, thereby reflecting the well-known presence of small-diameter regenerating muscle fibers (22). Although it has been suggested that T 2 variations represent a marker of muscle inflammation (33,34), it should be pointed out that a linear relationship of T 2 and intracellular volume has been previously reported (53).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These findings clearly showed that myeloid HIFs are not essential for skeletal muscle regeneration. Although the CTX-induced MRI changes observed in this study are in line with those recently reported in the literature (33), we further demonstrated that the increase of FA occurring 7 d after injury (33) was actually related to the decreased l 2 and l 3 values, thereby reflecting the well-known presence of small-diameter regenerating muscle fibers (22). Although it has been suggested that T 2 variations represent a marker of muscle inflammation (33,34), it should be pointed out that a linear relationship of T 2 and intracellular volume has been previously reported (53).…”
Section: Discussionsupporting
confidence: 93%
“…Although the CTX-induced MRI changes observed in this study are in line with those recently reported in the literature (33), we further demonstrated that the increase of FA occurring 7 d after injury (33) was actually related to the decreased l 2 and l 3 values, thereby reflecting the well-known presence of small-diameter regenerating muscle fibers (22). Although it has been suggested that T 2 variations represent a marker of muscle inflammation (33,34), it should be pointed out that a linear relationship of T 2 and intracellular volume has been previously reported (53). On that basis and considering the reduced second and third eigenvalues at day 7, the associated higher T 2 values might actually be related to the expansion of the extracellular component, including, for instance, a widened interstitial space (54,55), rather than to intracellular changes.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Magnetic resonance imaging (MRI) acquisition has been performed using a 7-T horizontal 30-cm bore, 300.3-MHz unit (BioSpec 70/30 USR, ParaVision 5.0; Bruker BioSpin, Karlsruhe, Germany) (23).…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%